2021
DOI: 10.1111/joms.12707
|View full text |Cite
|
Sign up to set email alerts
|

The Distinctive Domain of the Sharing Economy: Definitions, Value Creation, and Implications for Research

Abstract: The objective of this special issue is to expand our understanding of the sharing economy. To this end, we consider how the sharing economy can be demarcated and provide a definition that distinguishes the sharing economy from other forms of economic organization and resource orchestration. Specifically, the sharing economy entails multisided platforms that facilitate user access to – rather than ownership of – assets that are rivalrous in their use, and that are not owned by said platforms. Using this definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 40 publications
(41 reference statements)
1
8
0
1
Order By: Relevance
“…Finally, besides the peculiarities of SEPs versus other platforms (Markman et al, 2021), as noted earlier, the empirical context of our study (Chinese SEPs) further highlights the identified mechanisms for SEP success. In particular, the need for the on-demand adaptation of a SEP's resources and coordination with its ecosystem participants become more vital in emerging economies.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Finally, besides the peculiarities of SEPs versus other platforms (Markman et al, 2021), as noted earlier, the empirical context of our study (Chinese SEPs) further highlights the identified mechanisms for SEP success. In particular, the need for the on-demand adaptation of a SEP's resources and coordination with its ecosystem participants become more vital in emerging economies.…”
Section: Introductionsupporting
confidence: 72%
“…Many start-ups have been emerging as SEPs, utilizing multi-sided intermediation to facilitate exchanges between consumers and suppliers, thus creating value within their ecosystems (Belk, 2014;Matzler et al, 2015). However, despite the emerging studies on the sharing economy, we still lack an adequate understanding of the distinct characteristics of the platforms that operate in it and of their dynamics (Gerwe & Silva, 2020;Markman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan rumah adalah tempat untuk tinggal dan dengan pertumbuhan pendudukan yang pesat, maka industri properti mampu mengalami peningkatan, terlebih dalam masa pandemi [6]. Salah satu bidang industri properti yang telah menerapkan digital payment adalah AirBnB [7]. Dalam penelitian ini, objek penelitian terfokuskan pada Elin Kost, merupakan Kostan yang memiliki 43 kamar yang beralamat di Jalan Jati Gang Makmur Nomor 6 Desa Cimanganten Kecamatan Tarogong Kabupaten Garut.…”
Section: Pendahuluanunclassified
“…Another global trend altering the workplace context is the burgeoning of internet‐related technologies, such as the emergence of the platform or sharing economy in which “users, asset providers, and multisided platforms that facilitate temporary access to – rather than ownership of – assets that are rivalrous in their use, and that are not owned by said platforms” (Markman et al, 2021, p. 930). What does diversity mean to these newly emerged platform‐based firms?…”
Section: Propelling Research On Diversity In Management Studiesmentioning
confidence: 99%